Nicaragua : Joint Staff Assessment of the Poverty Reduction Strategy Paper Second Progress Report. (IMF Staff Country Reports; Country Report, 2004)
The current government has succeeded in reorienting economic policies after a series of shocks and an initial weak policy response. Revised real GDP growth targets are feasible with sustained prudent macroeconomic policies and institutional reforms. The medium-term macroeconomic framework centers on sustained prudent fiscal and monetary policies. The Poverty Reduction Strategy Paper (PRSP) could include a more detailed description of the actions being implemented to strengthen the financial system. The pursuit of fiscal discipline to restore macroeconomic stability has dominated the second year of strategy implementation.